2016
DOI: 10.7448/ias.19.1.20749
|View full text |Cite
|
Sign up to set email alerts
|

Transactional sex among young women in rural South Africa: prevalence, mediators and association with HIV infection

Abstract: IntroductionYoung adolescent women in sub-Saharan Africa are three to four times more likely to be HIV-positive than boys or men. One of the relationship dynamics that is likely to be associated with young women's increased vulnerability to HIV is transactional sex. There are a range of HIV-related risk behaviours that may drive this vulnerability. However, to date, limited epidemiological data exist on the role of transactional sex in increasing HIV acquisition, especially among young women in sub-Saharan Afr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 53 publications
6
61
1
Order By: Relevance
“…In these studies, transactional sex was included as a predictor, but it was not the focus of the analysis. However, in three studies, the primary objective was to assess the role of transactional sex on HIV [1921]. Of these three studies, one study used incident measures and was better able to assess the causal role of transactional sex in HIV risk [20].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In these studies, transactional sex was included as a predictor, but it was not the focus of the analysis. However, in three studies, the primary objective was to assess the role of transactional sex on HIV [1921]. Of these three studies, one study used incident measures and was better able to assess the causal role of transactional sex in HIV risk [20].…”
Section: Resultsmentioning
confidence: 99%
“…Five studies conducted among women [10,17,20,21,26] and four among men [17,2224] met the inclusion criteria for the meta-analyses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study in Wentworth, South Africa, revealed that both adolescent girls and boys were lured into transactional sex [65]. A qualitative study by Raganathan et al [66] in rural Bushbuckridge in Mpumulanga, South Africa, also found that young women perceived transactional sex as a way of securing financial success. The women from the study in Mpumulanga also viewed money and gifts as a determinant of a woman's value and the commitment of the man to her [66].…”
Section: Discussionmentioning
confidence: 99%